Antibiotics for acute respiratory infections in general practice: comparison of prescribing rates with guideline recommendations - McCullough, Amanda R; Pollack, Allan J; Plejdrup Hansen, Malene; Glasziou, Paul P; Looke, David FM; Britt, Helena C; Del Mar, Christopher B (Medical journal of Australia, 2017)
Objective: To compare the current rate of antibiotic prescribing for acute respiratory infections (ARIs) in Australian general practice with the recommendations in the most widely consulted therapeutic guidelines in Australia (Therapeutic Guidelines). Design and setting: Comparison of general practice activity data for April 2010 – March 2015 (derived from Bettering the Evaluation and Care of Health [BEACH] study) with estimated rates of prescribing recommended by Therapeutic Guidelines. Main outcome measures: Antibiotic prescribing rates and estimated guideline‐recommended rates per 100 encounters and per full‐time equivalent (FTE) GP per year for eight ARIs; number of prescriptions nationally per year. Results: An estimated mean 5.97 million (95% CI, 5.69–6.24 million) ARI cases per year were managed in Australian general practice with at least one antibiotic, equivalent to an estimated 230 cases per FTE GP/year (95% CI, 219–240 cases/FTE/year). Antibiotics are not recommended by the guidelines for acute bronchitis/bronchiolitis (current prescribing rate, 85%) or influenza (11%); they are always recommended for community‐acquired pneumonia (current prescribing rate, 72%) and pertussis (71%); and they are recommended for 0.5–8% of cases of acute rhinosinusitis (current prescribing rate, 41%), 20–31% of cases of acute otitis media (89%), and 19–40% cases of acute pharyngitis or tonsillitis (94%). Had GPs adhered to the guidelines, they would have prescribed antibiotics for 0.65–1.36 million ARIs per year nationally, or at 11–23% of the current prescribing rate. Antibiotics were prescribed more frequently than recommended for acute rhinosinusitis, acute bronchitis/bronchiolitis, acute otitis media, and acute pharyngitis/tonsillitis. Conclusions: Antibiotics are prescribed for ARIs at rates 4–9 times as high as those recommended by Therapeutic Guidelines. Our data provide the basis for setting absolute targets for reducing antibiotic prescribing in Australian general practice.